2022
DOI: 10.3390/polym14122405
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UV Light on the Barrier Performance of Aluminum Powder/Epoxy Coating

Abstract: Spherical aluminum powder was added to an epoxy composite coating in order to improve its protection performance for metal materials. The strength of the coating before and after UV (Ultraviolet Light) aging, its yellowing value, and its barrier properties were tested to explore the influence of UV light on the barrier performance of aluminum powder/epoxy coating. The results show that the addition of the aluminum powder enhanced the strength of the epoxy coating and reflected environmental UV light. This impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…, the readily mobile presence of humidity and the radiation induces the photo electron reduction of chemical chelates between studied dye and the fibers [17]. The aluminum containing compounds behave as a good barrier towards the UV radiation [18].…”
Section: Effect Of Uv/ozone Exposure On Tensile Strength and Elongationmentioning
confidence: 99%
See 1 more Smart Citation
“…, the readily mobile presence of humidity and the radiation induces the photo electron reduction of chemical chelates between studied dye and the fibers [17]. The aluminum containing compounds behave as a good barrier towards the UV radiation [18].…”
Section: Effect Of Uv/ozone Exposure On Tensile Strength and Elongationmentioning
confidence: 99%
“…In the spectrum ranging from wave number (400 to 4000) cm -1 , the distinct chemical groups of unexposed natural wool are evident. These include the amide group I at 1650 cm -1 , associated with the αhelical structure and C=O-stretch vibrations [13][14][15][16][17][18][19][20][21], amide group II at 1538 cm -1 , representing N-H bending and C-N-str. vibrations, and amide group III at 1230 cm -1 , indicating The UV/Ozone-aged samples show noticeable changes in the Amide I and Amide II regions, as shown in Fig.…”
Section: Ftir Analysismentioning
confidence: 99%
“…It has been reported that the addition of metal to the matrix can protect the matrix from degrading under UV radiation. The aluminum powder addition to epoxy is to be coated on any surface as a protection layer against UV radiation [69].…”
Section: 4mentioning
confidence: 99%
“…At the same time, the strong decomposition disablement of the main components caused by high energy ultraviolet (UV) is a fatal and unavoidable problem in the practical application for corrosion protection coatings. A common industrial solution to retard photo-aging of coatings is the addition of UV absorbers. These UV absorbers are organic sacrifice reagents and inevitably face the problems of poor stability and environmental pollution. Thus, the negative effects derived from the input energy to the coating and metal substrates would be reduced or eliminated. We can then impede the continuation of the corrosion reaction and increase the durability of the coating.…”
Section: Introductionmentioning
confidence: 99%